Demographic and psycho-social implications of forced eviction in Nigeria's megacity (2011)
This paper investigates the pattern and processes of forced eviction and homelessness among former residents of Aiyetoro, Lagos, Nigeria. Data were collected through questionnaire survey; in-depth interviews, unobtrusive observation and case-studies. The findings show that 89.7% of adult respondents reported different negative effects on their jobs; another 68.2% revealed their inability to pay children's school fees post-eviction, while 46. 7% of these children never attended school after the displacement episode. A high rate of family separation (27%) with its concomitant effects was also reported. The study argues that forced eviction hardly contributes to urban development and renewal often cited as justification. These evictions rather expose victims to harmful social, physical and mental processes and mal-adjustments that impinge on the health and demographic status of evictees culminating ultimately in expansion of the property-base of the rich through a reallocation strategy that excludes the poor.